Design of the automation system for the chemical water treatment plant of the oil refinery in Santiago de Cuba - Raidel Fidel Linares-Vicente; José Ricardo Nuñez-Alvarez; Mirlenis Montoya Alayo; Grether Lucía Real-Pérez (Universitas Ahmad Dahlan, 2025)
Production processes in modern industry demand higher levels of quality and efficiency in their products. The “Hermanos Díaz” Oil Refinery Company of Santiago de Cuba, a fundamental pillar in the economic and social development of the eastern part of the country, has a chemical water treatment plant responsible for supplying processed water to the industry’s boilers. The current state of this plant supports the lack of optimal physical-chemical conditions in the water it delivers and, therefore, the gradual deterioration of the boilers. This work conceives an automation solution for the dosing, precipitation, and clarification processes of the chemical water treatment plant. Control systems were designed based on instrumentation proposals, enabling reliable measurements and practical actions. In addition, an algorithm of supervision and automatic control using a programmable programmable logic controller (PLC) is presented, making the plant capable of delivering a product in optimal conditions. Images were designed for local and remote process control using a human-machine interface (HMI) panel and a supervisory control and data acquisition (SCADA) system. Finally, an automation architecture with a decentralized periphery is proposed to ensure safety and accuracy in the system’s decision-making through communication protocols.